Fetal growth surveillance – Current guidelines, practices and challenges - Williams, Mandy (Ultrasound, 2018)
Antenatal surveillance of fetal growth is an essential part of good maternity care, as lack of detection of fetal growth restriction is directly associated with stillbirth and perinatal morbidity. New algorithms and guidelines provide care pathways which rely on regular third trimester ultrasound biometry and plotting of estimated fetal weight in pregnancies considered to be at increased risk, and their implementation has increased pressures on ultrasound resources. Customised growth charts have improved the distinction between constitutional and pathological smallness and reduced unnecessary referrals. Their introduction, together with clinicians' training, e-learning and audit as the key elements of the growth assessment protocol, has resulted in increased antenatal detection of small for gestational age babies and a reduction in avoidable stillbirths. However, missed case audits highlight that further improvements are needed, and point to the need to address quality assurance and resource issues in ultrasound services.